Effect of dichotic presentation on speech intelligibility in the elderly - Kobayashi, Toshimitsu; Suzuki, Yôiti; Murase, Atsunobu; Sakamoto, Shuichi; Kawase, Tetsuaki; Nakajima, Fumie (AUDIOLOGY JAPAN, 2005)
Sensorineural hearing loss is commonly accompanied by reduced frequency selectivity and temporal resolution. The reduction of frequency selectivity engenders marked disadvantages through masking, particularly masking of middle and high frequency components by intense low frequency components: the so-called upward spread of masking. To reduce masking between contiguous frequency bands, we propose dichotic listening, in which frequency spectra are split into two complementary parts and presented dichotically. This way improve speech intelligibility. We studied the effect of dichotic listening on speech intelligibility in both quiet and noisy environments. Tests used vowel /u/-consonant-vowel nonsense syllables presented to four subjects with mild to moderate sensorineural hearing loss. In dichotic listening speech signals were divided into two frequency bands based on 5 the formant frequencies of Japanese vowels. (1) Results of speech intelligibility tests showed that speech intelligibility improved when the dividing frequency was 0, 8kHz (between F1 and F2 of Japanese vowel/u/). (2) The improvement in intelligility tends to increase with increasing speech-to-noise ratio.